2016
DOI: 10.16952/pns.2016.13.2.59
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Literature Review on Self-awareness Education/Training Programs in the Nursing Area

Abstract: Purpose: This paper is a review of interventions designed to promote self-awareness in the nursing area. The specific purpose was to analyze the general characteristics of self-awareness intervention studies, intervention contents, and the effects of the studies in order to present basic information for developing self-awareness interventions in the nursing area. Methods: Using "nurse/nursing" and "self-awareness" as key words, the researchers searched six electronic databases. The method proposed by Whittemor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 29 publications
3
14
0
Order By: Relevance
“…The core finding is that nurses apply and use self-awareness in clinical practice in a moderate manner, and the levels of self-awareness are positively associated with their age and years of clinical and educational experiences. This finding is consistent with the previous literature that clinical experiences and the application of learning gained from previous experiences enhance nurses’ self-awareness (Han & Kim, 2016; Younas et al, 2019). Despite the significant role of, need for, and use of therapeutic self in clinical settings (Jack & Miller, 2008; Ramvi, 2015; Han & Kim, 2016), the nurses in this study had moderate levels of self-awareness.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The core finding is that nurses apply and use self-awareness in clinical practice in a moderate manner, and the levels of self-awareness are positively associated with their age and years of clinical and educational experiences. This finding is consistent with the previous literature that clinical experiences and the application of learning gained from previous experiences enhance nurses’ self-awareness (Han & Kim, 2016; Younas et al, 2019). Despite the significant role of, need for, and use of therapeutic self in clinical settings (Jack & Miller, 2008; Ramvi, 2015; Han & Kim, 2016), the nurses in this study had moderate levels of self-awareness.…”
Section: Discussionsupporting
confidence: 93%
“…Possibly, the situation at the global level is similar. Han and Kim (2016) identified that most educational and professional development interventions on self-awareness include students as the target groups. Given this, it is noteworthy to highlight the need for a greater focus on self-awareness of nurses in practice settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Becoming self‐aware does not only help nurses in developing a therapeutic and interpersonal relationship, but also enable them to improve their critical thinking and clinical decision‐making skills (Han & Kim, ; Jack & Smith, ). It also helps nurses to determine their roles and responsibilities in a given situation and discern appropriate nursing actions.…”
Section: Introductionmentioning
confidence: 99%
“…The first step towards self-care is becoming resilient. It involves an objective examination of oneself through introspection by ensuring that an individual knows own thoughts, feelings, beliefs, values, behaviours, and feedback from others [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%